2016
DOI: 10.1097/md.0000000000003800
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Intervention Improves Survival for Metastatic Non-Small Cell Lung Cancer Patients

Abstract: Surgical intervention for stage IV non-small cell lung cancer (NSCLC) is still controversial. This study sought to evaluate the clinical effects of surgical intervention on survival in patients with stage IV NSCLCs and to identify the cohort benefitting the most from surgery.A retrospective study from the Surveillance, Epidemiology, and End Results database was performed to compare the survival of stage IV NSCLC patients who had undergone surgery with those who did not undergo surgery. Overall survival (OS) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 20 publications
4
13
0
Order By: Relevance
“…Marital status, sex, race, age, histology, T stage, N stage, histological differentiation, the presence of bone metastasis, brain metastasis, liver metastasis, M1a disease, surgery of primary cancer, and chemotherapy were identified as the prognostic factors of the OS, which was in line with the previous studies. 5 , 7 , 8 , 11 , 16 18 Among them, surgery of primary cancer could notably improve the prognosis. Thus, we analyzed the characteristics of these patients who underwent surgery and found that all of them received radiation therapy, and most of them received chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marital status, sex, race, age, histology, T stage, N stage, histological differentiation, the presence of bone metastasis, brain metastasis, liver metastasis, M1a disease, surgery of primary cancer, and chemotherapy were identified as the prognostic factors of the OS, which was in line with the previous studies. 5 , 7 , 8 , 11 , 16 18 Among them, surgery of primary cancer could notably improve the prognosis. Thus, we analyzed the characteristics of these patients who underwent surgery and found that all of them received radiation therapy, and most of them received chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In reality, metastatic lung cancer is a heterogeneous disease with various prognoses, 3 which are affected by physical conditions of patients, such as age, sex, marital status, performance status as well as the TN stage, pathological or genotype characteristics, type of metastatic organ, number of metastatic sites, and medical treatments. 2 8 Estimating prognosis of every patient accurately may benefit patients and doctors alike in all aspects of decision-making. 9 The TNM stage released by International Association for the Study of Lung Cancer International Staging Project is widely accepted as a tool to predict the prognosis of patients and had been updated to the eighth edition.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is mainly classified into two tissue subtypes as non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC). NSCLC accounts for ~80% of lung cancer, including adenocarcinoma, squamous cell carcinoma and large cell carcinoma ( 4 ). Currently, surgical resection combined with chemotherapy and radiotherapy is still the main means of clinical treatment for lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, great progress has been made in the diagnosis of and clinical therapy for lung cancer. However, the mortality rate of patients with lung cancer remains high, with a 5-year survival rate of only 15% (25)(26)(27). Oridonin is a compound that is extracted from the traditional Chinese herb R. rubescens, which possesses anticancer properties through inhibiting proliferation and promoting apoptosis (24,28,29).…”
Section: Discussionmentioning
confidence: 99%